Antifungal Activity of Amphotericin B Cochleates against Candida albicans Infection in a Mouse Model - Zarif, Leila (American Society for Microbiology, 2000)
Cochleates are lipid-based supramolecular assemblies composed of natural products, negatively charged phospholipid, and a divalent cation. Cochleates can encapsulate amphotericin B (AmB), an important antifungal drug. AmB cochleates (CAMB) have a unique shape and the ability to target AmB to fungi. The minimal inhibitory concentration and the minimum lethal concentration against Candida albicans are similar to that for desoxycholate AmB (DAMB; Fungizone). In vitro, CAMB induced no hemolysis of human red blood cells at concentrations of as high as 500 μg of AmB/ml, and DAMB was highly hemolytic at 10 μg of AmB/ml. CAMB protect ICR mice infected with C. albicans when the agent is administered intraperitoneally at doses of as low as 0.1 mg/kg/day. In a tissue burden study, CAMB, DAMB, and AmBisome (liposomal AmB; LAMB) were effective in the kidneys, but in the spleen CAMB was more potent than DAMB at 1 mg/kg/day and was equivalent to LAMB at 10 mg/kg/day. In summary, CAMB are highly effective in treating murine candidiasis and compare well with AmBisome and AmB.